The Impact of Tenth Grade Students’ Grammar Mastery and Anxiety on Their English Achievement - Febriyanti, Nani; Sari, Artanti Puspita; Firdaus, Masagus (Journal of Social Work and Science Education, 2023)
The aim in the study is to comprehend and determine how students’ anxiety and ability to use grammar influence their English achievement in the X-grade at three schools in the districts of Semendawai Barat and Cempaka, OKU East regency. For this study, ex post facto design was applied. At SMA N 1 Cempaka, SMA N 2 Semendawai West, and SMA N 1 Semendawai West, this research was carried out. The 96 participants from 3 different schools made up the sample. In this study, several data testing methods were employed, including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, autocorrelation tests, correlation studies of the r-product moment, simple regression analyses, and double regression analyses. The findings of this study demonstrated that: 1) grammar proficiency significantly influences English success; 2) The achievement of students in English has been considerably impacted by students’ worry; and 3) Although only by 10.8%, grammatical proficiency and anxiety together have a considerable impact on English learning outcomes.